Morphological and anatomical characters variation of Indigofera accessions from Java, Indonesia - MUZZAZINAH MUZZAZINAH; Suratman SURATMAN; NURMIYATI NURMIYATI; SRI RETNO DWI ARIANI (Society for Indonesian Biodiversity, 2021)
Abstract. Muzzazinah, Suratman, Nurmiyati, Ariani SRD. 2021. Morphological and anatomical characters variation of Indigofera accessions from Java, Indonesia. Biodiversitas 22: 2104-2116. The objective of this research was to evaluate morphological and anatomical character variation of Indigofera accessions from Java, Indonesia. A total of 15 accessions from three species of Indigofera were collected from centers of Batik manufacturing in Java located in the following locations: West Java (Pangandaran), Yogyakarta (Bantul, Kulonprogo), Central Java (Sragen, Sukoharjo, Karanganyar) and East Java (Tuban). There were 14 tested morphological characters based on measurement of vegetative and generative organs. Anatomical characters were observed from paradermal sections and there were 12 tested characters. Analysis of variance was performed for observed morphological and anatomical characters data in order to test the significance of variation among accessions using SPSS software. The characters' mean values then were used to perform principal component analysis and cluster analysis using PAST software. A cluster analysis was conducted by applying an Unweighted Pair Group Method with Arithmetic Averages (UPGMA) in order to group the accessions based on morphological and anatomical character similarity. The analysis of variance for the evaluated morphological and anatomical characters revealed highly significant differences among accessions for all of the tested characters suggesting that there was a high degree of phenotypic diversity among Indigofera accessions. Principal component analysis indicated that the first 2 components accounted for 90.72 % and 88.96 % of the total variation for morphological and anatomical data sets, respectively. Cluster analysis using morphological characters data revealed three main clusters. Four main clusters were then highlighted in cluster analysis of the anatomical character data. The grouping of the accession into clusters showed that there was no correlation between ecological habitat origin and the character diversity expressed among Indigofera accession. However, accessions that came from the same species had the tendency to cluster together.